Bahasa, Identitas, dan Konflik - Katubi Obing (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2010)
In popular observation, the relation between language and conflict to date is set aside. However, in various conflicting areas, linguistic conflicts are frequently taking place, for instance the disputes over the use of languages. In relation to identity construction, in a certain state, language policy is the heart of formation of national identity. Due to the important role of language, when language is related to some aspects of human life; language can be politicized as well as cause a conflict. This paper discusses a number of historical evidence about repression upon language due to the conflict , language conflict and national identity. Based on a number of historical evidences, it can be argued that a language can become a victim of conflict due to the assumption that language loyalty can overcome loyalty towards the state. At the same time, language can be utilized as a symbol of struggle in an effort to separate itself from the state. In addition it can also serve as a separating symbol among the conflicting groups t. Language conflict can occur either in monolingual or multilingual communities. d The heterogeneity and the similarity of language can be constructed to maximize language as a symbol of identity in line with socio-political changes accompanying the conflict.Keywords: language conflict, identity, language politisation, language discrimination, language policy